Mobile App Prototype for Course Management in Secondary Education - Valdez Joo Aquije, Eric; Palacios Vergara, Greyh; Herrera Salazar, Jose Luis; Andrade-Arenas, Laberiano (International Journal of Interactive Mobile Technologies (iJIM), 2023)
In the last decade, mobile applications have shown an expansion to a great diversity of uses that can be made, which has influenced at different levels (economic, cultural, political), as in the area of learning where it has played a very important role in learning, since now with the development of technologies, children and adolescents are very interested in these new technologies and it is easier for them to use them, which also supports them in learning a great diversity of subjects of their own interest. That is why in this work a prototype of a mobile application for the management of mobile education using the Scrum methodology at the Norbert Wiener University of Lima-Peru, knowing that there are learning problems in students in the classroom, for this, want to provide a mobile application that supports the student to improve their learning. As a result, obtained from the study, was a prototype of a mobile application to improve learning in the Monte Carmelo private school in Lima-Peru, where a virtual model of the mobile application is shown, register the user, login where you can view their classes and share their class assignments, facilitating the user to enter their class and study material, this was achieved using balsamiq, the Scrum methodology with its four phases. The results of the survey conducted to the experts show that in most of the questions they gave a high scale, with the highest average of 4.91 with a standard deviation of 0.302 and only one low scale obtained of 1.45 on average with a standard deviation of 0.52.